2001
DOI: 10.1161/hc3601.095576
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 1 Receptor Blockade Prevents Lethal Malignant Hypertension

Abstract: Background-Angiotensin II is elevated in malignant hypertension. We tested the hypothesis that angiotensin II type 1 receptor blockade can prevent the development of malignant hypertension even in the absence of a blood pressure-lowering effect. Methods and Results-Two-kidney, 1-clip rats were followed up for 28 days; blood pressure was measured by tail-cuff plethysmography and intra-arterially. After a 2-week run-in phase, rats received valsartan at a dose of 0.3 (nϭ14) or 3 (nϭ12) mg · kg Ϫ1 · d Ϫ1 or solven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 34 publications
3
51
0
1
Order By: Relevance
“…Members of the HSP family are able to stimulate cells of the innate immune system directly and act as dangersignaling molecules (Hilgers et al, 2001). Proinflammatory cytokines induce activation of HSF1-DNA binding followed by induction of HSP70 expression (Schett et al, 1998).…”
Section: ##mentioning
confidence: 99%
“…Members of the HSP family are able to stimulate cells of the innate immune system directly and act as dangersignaling molecules (Hilgers et al, 2001). Proinflammatory cytokines induce activation of HSF1-DNA binding followed by induction of HSP70 expression (Schett et al, 1998).…”
Section: ##mentioning
confidence: 99%
“…Activation of the renin-angiotensin system is a major cause of systemic hypertension and local activation in the kidneys induces renal tissue damage via immunological mechanisms such as the activation of nuclear factor κB (NFκB) (6). In addition, renal monocyte chemoattractant protein-1 expression is increased in an experimental rat model of renin-angiotensin system-dependent hypertension, and angiotensin II type 1 receptor blocker inhibits the production of monocyte chemoattractant protein-1 protein and decreases macrophage infiltration (7). Furthermore, large clinical trials have confirmed that angiotensin-converting enzyme inhibitors inhibit the renin-angiotensin system, and that angiotensin II type 1 receptor blockers have renoprotective effects in diabetic and non-diabetic renal diseases, with some of these renoprotective effects appearing to be independent of the blood pressure-lowering effects (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, all 16 patients were clinically and histologically diagnosed with benign hypertensive nephrosclerosis. Human benign hypertensive nephrosclerosis is thought to develop gradually as a consequence of long-term hypertension, and thus shows a considerably different progression from experimental hypertension, which is generally rapid and short-term (4,5,7). The present data are interesting, because they suggest that, in addition to the role played by the renin angiotensin system, an inflammatory process could also contribute to the progression of human benign hypertensive nephrosclerosis, although the mechanisms are not likely to completely correspond with those in experimental models.…”
mentioning
confidence: 99%
“…2,3 Hypertension is with dyslipidemia and platelet activation a major contributor to cardiovascular risk 4 with clinical consequences, such as heart failure, acute coronary syndrome and ischemic stroke. 5,6 It was therefore thought useful to test whether OBL also had any effects on blood pressure in a model of experimental hypertension and cardiac hypertrophy. …”
mentioning
confidence: 99%